Barriers to not informing patients about radiation in connection with radiological examinations: Radiographers' opinion. Issue 2 (May 2020) - Ukkola, L.; Kyngäs, H.; Henner, A.; Oikarinen, H.
Abstract: Introduction: In some instances, little knowledge regarding radiological examinations is provided to patients. The purpose was to investigate whether radiographers inform patients about radiation, and if not, the reasons for it. Methods: A questionnaire was sent to radiographers working in the public sector in Northern Finland. Radiographers were asked whether they had informed patients about the radiation dose and risks during the last year. If information was not provided, the reasons for it were investigated using multiple-answer type multiple-choice questions with the option for free text responses. The results were compared between a University Hospital and other departments and between different lengths of work experience. Altogether 174/272 (64%) radiographers responded to the questionnaire; 50% were from the University Hospital and 50% from other departments. Results: Altogether 103/174 (59%) respondents did not inform patients about the radiation dose and 93/174 (53%) did not inform them about the associated risks. Regarding a passive approach to dose information, respondents thought that the referrer had already informed the patient (49/103, 48%), information was not needed (51/103, 50%), or it might cause unnecessary fear (47/103, 46%). Reasons for a passive approach to risk information were similar (66/93, 71%; 33/93, 36%; 47/93, 51%, respectively). Regarding the results, there were no differences between the institutions or work experience levels. According to the open question, some radiographers expected patients to ask questions before informing them. Lack of time was rarely mentioned as a reason. Conclusion: The main reasons for inadequate information were ignorance regarding responsibilities, assumption that information is not needed, and concern about causing unnecessary fear. Implications for practice: Education, guidelines specifying responsibilities and contents for information, and easy-access digital educational material for public and professionals are needed.